Implementation of EDFAT Technique in the Creation of Photo Story about Galeri Foto Jurnalistik Antara - Alyatalatthaf, Muhammad Dicka Ma'arief; Kusumawati, Dyah (Rekam, 2023)
Photo story is a genre in photography which aims to capture various life events with a chronological plot that has a narrative aspect. It is enable us to tell a story in several photo that represent reality holistically. A photography technique known as EDFAT is also used to aid in the creation of works. The goal of this research is to use the EDFAT technique to create photo story works at Galeri Foto Jurnalistik Antara. The results of this study, "Galeri Foto Jurnalistik Antara" photo story is able to accommodate photos that are holistic visually and narratively due to the implementation of EDFAT: a) Entire, producing photos of locations, situations, events, activities, and objects that represent GFJA and Graha Bhakti Museum; b) Detail, produce photos of specific parts of the GFJA, the important elements in it are described in close-up and isolated through DOF; c) Frame, produces photos that highlight objects by utilizing the foreground and being able to frame discourse through visuals; d) Angle, produce photos with an unusual perspective so that the audience can enjoy objects from a unique perspective; e) Time, produce photos that philosophically want to describe the activities of visitors at GFJA.